Synthesis and characterization of biodegradable amphiphilic ABC Y‐shaped miktoarm terpolymer by click chemistry for drug delivery. Issue 23 (24th September 2014) - Chu, Yanfeng; Yu, Huan; Zhang, Yunti; Zhang, Guangyan; Ma, Yingying; Zhuo, Renxi; Jiang, Xulin
ABSTRACT Biodegradable amphiphilic ABC Y‐shaped triblock copolymer (MPBC) containing PEG, PBLA, and PCL segments was synthesized via the combination of enzymatic ring‐opening polymerization (ROP) of epsilon‐caprolactone, ROP of BLA‐N‐carboxyanhydride and click chemistry, where PEG, PBLA, and PCL are poly(ethylene glycol), poly(benzyl‐l‐aspartate), and polycaprolactone, respectively. Propynylamine was employed as ROP initiator for the preparation of alkynyl‐terminated PBLA and methyloxy‐PEG with hydroxyl and azide groups at the chain‐end was used as enzymatic ROP initiator for synthesis of monoazido‐midfunctionalized block copolymer mPEG‐b‐PCL. The subsequent click reaction led to the formation of Y‐shaped asymmetric heteroarm terpolymer MPBC. The polymer structures were characterized by different analyses. The MPBC terpolymer self‐assembled into micelles and physically encapsulated drug doxorubicin (DOX) to form DOX‐loaded micelles, which showed good stability and slow drug release. In vitro cytotoxicity study indicated that the MPBC micelles were nontoxic and the DOX‐loaded micelles displayed obvious anticancer activity similar to free DOX against HeLa cells. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3346–3355